2022
DOI: 10.3389/fendo.2022.841971
|View full text |Cite
|
Sign up to set email alerts
|

Positive Effects of Extra-Virgin Olive Oil Supplementation and DietBra on Inflammation and Glycemic Profiles in Adults With Type 2 Diabetes and Class II/III Obesity: A Randomized Clinical Trial

Abstract: BackgroundEvidence on the effects of dietary interventions on inflammatory markers in individuals with obesity and type 2 diabetes mellitus (T2DM) is scarce. Our study evaluated the effects of extra-virgin olive oil alone and in combination with a traditional Brazilian diet on inflammatory markers and glycemic profiles in adults with both T2DM and class II/III obesity.MethodsAdults aged 18-64 years with T2DM and class II/III obesity were randomized into two intervention groups: 1) extra-virgin olive oil only a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…The combined action of MUFA and polyphenol components on different metabolic pathways may contribute positively to control lipid metabolism, favor good glycemic control, and ensure good anti-inflammatory activity. Table 1 summarizes the main studies on the direct effect of OO intake on metabolic studies [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The combined action of MUFA and polyphenol components on different metabolic pathways may contribute positively to control lipid metabolism, favor good glycemic control, and ensure good anti-inflammatory activity. Table 1 summarizes the main studies on the direct effect of OO intake on metabolic studies [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…The EVOO+DieTBra groups also showed decreased BMI, weight, serum levels of inflammatory cytokines, interleukin-1α (IL-1α), and adiponectin, as well as increased tumor necrosis factor α (TNF-α). This study concluded that EVOO+DieTBra has a role in ameliorating the inflammatory profiles and fasting insulin levels of adults having class II/III obesity and T2D [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a recent survey with the Brazilian diet, positive results were also found 26 , a study was carried out that evaluated the effects of extra virgin olive oil alone and in combination with a traditional Brazilian diet on inflammatory markers and glycemic profiles in adults with DM2 and class II obesity/ III. The intervention with Olive Oil + Brazilian Diet effectively decreased the levels of fasting insulin, IL-1α and adiponectin, suggesting its beneficial role in improving inflammatory profiles and fasting insulin levels in adults with class II/III obesity and T2DM.…”
Section: Source: Authors 2022mentioning
confidence: 99%